Cytomegalovirus Seroprevalence as a Risk Factor for Poor Outcome in Acute Respiratory Distress Syndrome*. Issue 2 (February 2015) - Ong, David S. Y.; Klein Klouwenberg, Peter M. C.; Verduyn Lunel, Frans M.; Spitoni, Cristian; Frencken, Jos F.; Dekker, Huberta A. T.; Schultz, Marcus J.; Bonten, Marc J. M.; Cremer, Olaf L.
<x xml:space="preserve">Abstract</x> Objective: Cytomegalovirus reactivation may complicate critical illness in latent carriers of the virus, even in patients who were previously immunocompetent. Patients with acute respiratory distress syndrome are considered to be prone for reactivation. Prophylactic antiviral therapy in immunocompetent cytomegalovirus seropositive patients admitted to the ICU with acute respiratory distress syndrome has therefore been proposed. We assessed cytomegalovirus seroprevalence as a risk factor for morbidity and mortality in patients with acute respiratory distress syndrome. Design: Prospective observational cohort study. We used the number of days alive and free of mechanical ventilation on day 28 as a composite outcome measure and used multivariable ordinal logistic regression analyses to adjust for potential confounders. Setting: ICUs of two tertiary care hospitals in The Netherlands. Patients: We included all newly admitted patients with acute respiratory distress syndrome who received mechanical ventilation for at least 4 days. Patients with known immunocompromise and those receiving antiviral treatment prior to ICU admission were excluded. Interventions: None. Measurements and Main Results: Over a 2-year period, 306 patients were included, 209 (68%) of whom were cytomegalovirus seropositive. Cytomegalovirus reactivation occurred in 53 of these cases (26%). One hundred patients (33%) died or continued to be mechanically ventilated by day 28. After adjustment for confounding, cytomegalovirus seroprevalence was not associated with the primary outcome (crude odds ratio, 1.09; 95% CI, 0.70–1.70; adjusted odds ratio, 1.01; 95% CI, 0.64–1.59). Seroprevalence was also not associated with poor outcome in any of the prespecified subgroup analyses. However, a significant association was found in a post hoc subgroup of patients who had developed acute respiratory distress syndrome in a setting of septic shock (adjusted odds ratio, 2.86; 95% CI, 1.32–6.23). The time course of pulmonary markers in survivors was comparable between the two serogroups. Conclusions: Cytomegalovirus seroprevalence is not associated with prolonged mechanical ventilation or increased mortality in critically ill patients with acute respiratory distress syndrome, with possible exception of patients presenting with septic shock. Therefore, a prevention strategy targeting an unselected cohort of seropositive patients with acute respiratory distress syndrome is unlikely to show any meaningful benefit.